Occupational Therapy to Make Paints from Used Bottles at The Civil Social Residence Foundation, Batam City - Noer, Rachmawaty M.; Junaidah, Junaidah; Somad, Abdul; Yopanti, Enie; Yanawati, Yanawati; Mayasari, Efrida; Wahyuningsih, Endang; Agusrianti, Agusrianti; Cem, Caroline (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Elderly is the population aged 60 years or more. Lasnia is a condition that takes place in human life. The elderly will experience some setbacks both physically, psychologically, and cognitively. One way to maintain the psychological function of the elderly to remain stable is by doing occupational therapy which has the aim of increasing the ability of the elderly to produce a product of art so that it fills the spare time for the elderly. Purpose. This quantitative study aimed to Free time that is not used will cause boredom and boredom in the elderly. So making piggy bank skills from used bottles is one of the occupational therapies that will be taught to the elderly to reduce the level of stress and boredom experienced by the elderly living in an orphanage. Method. This activity was carried out on Saturday, April 15, 2023, at the Budi Social Foundation for the Elderly, which was attended by 17 elderly people. The activity is carried out by making piggy bank crafts using used bottles. Results. The implementation of the activity consists of four stages, namely the identification, planning, implementation, and evaluation stages. The results of the evaluation of this activity show that the elderly can produce works of art and make piggy bank creations using used bottles. Conclusion. The elderly looked happy and enthusiastic when they took part in the activities carried out by the Nursing Profession students at Awal Bros University.